2021
DOI: 10.14202/vetworld.2021.1529-1536
|View full text |Cite
|
Sign up to set email alerts
|

Marsilea crenata ethanol extract prevents monosodium glutamate adverse effects on the serum levels of reproductive hormones, sperm quality, and testis histology in male rats

Abstract: Background and Aim: Marsilea crenata is an aquatic plant that contains high antioxidants level and could prevent cell damages caused by free radicals. The present study aimed to investigate the effect of M. crenata ethanol extract on luteinizing hormone (LH), testosterone levels, sperm quality, and testis histology of adult male rats induced by monosodium glutamate (MSG). Materials and Methods: This study randomly divided 48 male rats into eight groups (n=6): control group; MSG group (4 mg/g body weight [b.w.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Several laboratory studies had reported that plants suggested to have high flavonoids and with high antioxidant properties decreases the reactive oxygen species reportedly generated from the consumption of MSG. A study had recently reported that the high antioxidant level and the active compound contained in some plants can improve the negative effect of MSG in male reproductive functions ( Rahayu et al, 2021 ). Khaled et al ( Khaled et al, 2016 ) examine the protective effect of propolis on MSG-induced reproductive toxicity and suggested that propolis can be effective in the protection of MSG-induced reproductive toxicity.…”
Section: The Protective Role Of Natural Antioxidants In Msg Induced T...mentioning
confidence: 99%
“…Several laboratory studies had reported that plants suggested to have high flavonoids and with high antioxidant properties decreases the reactive oxygen species reportedly generated from the consumption of MSG. A study had recently reported that the high antioxidant level and the active compound contained in some plants can improve the negative effect of MSG in male reproductive functions ( Rahayu et al, 2021 ). Khaled et al ( Khaled et al, 2016 ) examine the protective effect of propolis on MSG-induced reproductive toxicity and suggested that propolis can be effective in the protection of MSG-induced reproductive toxicity.…”
Section: The Protective Role Of Natural Antioxidants In Msg Induced T...mentioning
confidence: 99%
“…Subsequently, a stain containing 1% Eosin and 5% Negrosin was added. The percentage of spermatozoa viability and abnormalities were observed under a light microscope at a magnification of 400x, following the formula [1] :…”
Section: Viability and Abnormality Spermatozoamentioning
confidence: 99%
“…Recommended MSG consumption for Asian countries ranges from 1.2 to 1.7 g daily. However, MSG consumption in Indonesia has increased to 4.32 g per day [1]. This increase in MSG consumption can trigger physiological disturbances in the body, particularly within the reproductive system.…”
Section: Introduction mentioning
confidence: 99%
“…Abd [39] found that 14 days of MSG treatment at a dose of 4 mg/g BW could produce up to 62% increase in spermatozoa abnormalities. MSG also causes an abnormal sperm number from 27.97% to 37.83% [40]. Excess glutamate in the body enhances intracellular Ca 2+ levels in mitochondria, disrupting mitochondrial ATP synthesis and increasing ROS concentrations [41].…”
Section: Table 2 the Sperm Quality Of Mice In All Treatment Groupsmentioning
confidence: 99%